Evaluation of Hevea brasiliensis clones for yielding trends in Tripura - Priyadarshan P M; Dey S K; Sasikumar S; Sudhasowmyalatha M K; Varghese Y A (Indian Journal of Natural Rubber Research, 2000)
A comparison of two yielding regimes of Hevea brasiliensis (Regime I - April to September - non-cold season and Regime II - October to January - cold season) with respect to 15 clones of varying yield potential evaluated in Tripura, indicated a congenial environment for yield in the cold season. The clones PB 235, RRII 118, RRII 203, RRIM 600 and RRIM 703 were ranked as high yielders considering the data from BO1 and BO2 panels. Among these, RRII 203 and PB 235 exhibited least depression in yield (18.6 and 31.9;respectively) during Regime I. In general, dry rubber yield showed negative relationship with minimum temperature, wind velocity and evaporation. However, PB 235 lacked any such relationship when considered individually, indicating thereby that it is less sensitive to yield stimulation towards the onset of cold season. The mean dry rubber yields, (g/tree/tap) of PB 235 and RRIM 600 were regressed against environmental mean under the two regimes. Accordingly, 28 (g/tree/tap) was identified as the threshold yield under stress. In terms of yield per cm of tapping cut, PB 235, RRIM 703, RRII 203 and RRII 118 were found to be potential yielders. Covariance analysis categorised RRII 5, RRIM 703, PB 5/51 and PB 235 to be consistent over the regimes. Considering the attributes mean yield, per cent depression during Regime I, yield per unit length of tapping cut and consistency in yield over regimes, clones selected for commercial evaluation are PB 235, RRII 203, RRII 118 and RRIM 703 with RRIM 600 as check.
Keywords: Consistency; Consistency; Non-traditional environment; Non-traditional environment; Stress factors; Stress factors; Yield depression; Yield depression; Yield regimes; Yield regimes